Bibliometric Analysis of Sustainability in Science Education - Yanti Hadiyati (Journal of Education for Sustainable Development Studies, 2024)
Currently, the word sustainability is increasingly being used as a narrative that leads people to carry out the vision of an environmentally friendly lifestyle. This study presents a bibliometric analysis of 498 documents from 2001 to 2022 from the Scopus database using inclusion and exclusion criteria and visualization using the Vos Viewer. Although the first research was conducted in 2001, most of the research was published in 2021-2022. The literature on sustainability is growing significantly and this pattern is expected to increase in 2022 and beyond. Data analysis including publication developments and citation trends, most cited documents, most prolific sources, most prolific institutions, most prolific authors, most prolific countries, Keyword-based and co-authoring development maps for publications for authors and countries. The findings show that 2021 has the highest number of publications on Sustainability in Science Education with 70 documents and 184 citations, while 2019 has the highest number of citations, namely 668 citations with a total of 51 documents. The most cited documents are written by Snively, G., et al., with 252 citations and an average (C/Y) of 12 per year. The most productive source comes from Sustainability (Switzerland) which has published 43 documents, 397 citations, and 29 TLS. The most productive institution comes from the Universitat Bremen, Germany with 29 documents. The most prolific author is Eilks, I., who comes from Germany with a total of 26 documents and 598 citations. Eilks, I., also has a strong collaboration network between authors. The most productive country is topped by the United States with 154 documents, and 1681 citations. The United States, Germany, and the United Kingdom are the countries that have collaborated the most with other countries. This research maps out scientific publications on Sustainability in Science Education that will be useful for future collaborations and provide a framework for future research.